899. Reduction of Surgical Site Infections Post Cesarean Section through Implementation of Novel Evidenced Based Bundle - Vacca, Maria (Open Forum Infect Dis, 2020)
BACKGROUND: A frequent complication post cesarean section (C-section) is surgical site infections (SSI) which are associated with heightened maternal morbidity and mortality, decreased patient satisfaction, prolonged hospitalization, and increased costs. In Calendar Year 2019, our Infection Control Committee identified an increase in the incidence of post-operative C-section SSI rates over an 8 month period from January through August of 2019.. The purpose of this study was to develop, implement and measure the compliance and efficacy of a novel pre-operative bundle (POB) for patients undergoing C-section. Calendar Year 2019 Jan. through Aug. C-Section Infections Raw Numbers [Image: see text] METHODS: In October 2019, our multidisciplinary team consisting of Infection Control, Pharmacy, Nursing, and Physicians developed and implemented POB for patients undergoing C-section. The POB included the following: 1. Mandatory interventions of vaginal cleansing using povidone iodine 2. Chlorhexidine (CHG) 2% wipes to abdomen 3. Addition of Azithromycin 500mg x 1 dose as pre-operative antibiotic. Primary endpoint of the study was to measure the overall C-section SSI incidence for 8 months period pre and 8 months post implementation of the POB. This Secondary endpoint of the study included POB compliance and efficacy of real-time prospective audit and feedback for non-compliance. Novel Preoperative Bundle Auditing Compliance [Image: see text] RESULTS: There were total of 212 patients who received C-section in Pre-POB group and 182 in Post-POB group. Baseline characteristics between the groups were similar. Overall C-section rates Pre-POB was 3.8 % vs 0% in Post-POB group. We noted a bundle compliance of 97.9% since implementation of POB. Real time prospective audit and feedback was provided to total of 122 cases after implementation of POB. Comparison of C-Section Raw Numbers Calendar Year 2019 Pre and Post Novel Bundle Implementation [Image: see text] CONCLUSION: With implementation of POB, we noticed a significant drop in our C-section SSI. We observed a very high bundle compliance with implementation of prospective audit and feedback approach. This is the first study evaluating implementing a novel pre-operative bundle for patients undergoing C-section. Continued auditing and real time feed back of novel bundle will ensure continued success. DISCLOSURES: All Authors: No reported disclosures